The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1001/jama.2011.1703
|View full text |Cite
|
Sign up to set email alerts
|

Dosing Clopidogrel Based on CYP2C19 Genotype and the Effect on Platelet Reactivity in Patients With Stable Cardiovascular Disease

Abstract: clinicaltrials.gov Identifier: NCT01235351.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
225
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 328 publications
(250 citation statements)
references
References 34 publications
11
225
1
9
Order By: Relevance
“…Besides acting as a vasodilator, riociguat promotes platelet inhbition by acting synergistically with PGI 2 75. The state of inhibitory pathways can be monitored by measuring intracellular phosphorylation of the PKA/PKG substrate protein VASP in platelets, which has been used to study the efficiency of P2Y12 inhibition in patients 109, 110. Pharmacological studies of P2Y12 receptor based anti‐platelet therapy show that addition of low concentrations of PGI 2 and NO to platelets from volunteers receiving dual anti‐platelet therapy with aspirin and the P2Y12 blocker prasugrel strongly enhances platelet inhibition in the presence of TRAP‐6 or collagen 8.…”
Section: Discussionmentioning
confidence: 99%
“…Besides acting as a vasodilator, riociguat promotes platelet inhbition by acting synergistically with PGI 2 75. The state of inhibitory pathways can be monitored by measuring intracellular phosphorylation of the PKA/PKG substrate protein VASP in platelets, which has been used to study the efficiency of P2Y12 inhibition in patients 109, 110. Pharmacological studies of P2Y12 receptor based anti‐platelet therapy show that addition of low concentrations of PGI 2 and NO to platelets from volunteers receiving dual anti‐platelet therapy with aspirin and the P2Y12 blocker prasugrel strongly enhances platelet inhibition in the presence of TRAP‐6 or collagen 8.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively increasing clopidogrel dose may sometimes suffice. Among patients with stable cardiovascular disease, tripling the maintenance dose of clopidogrel to 225 mg daily in CYP2C19*2 heterozygotes, achieved levels of platelet reactivity similar to that seen with the standard 75 mg dose in non-carriers; for CYP2C19*2 homozygotes, doses as high as 300 mg daily did not result in comparable degrees of platelet inhibition [5]. …”
mentioning
confidence: 83%
“…Recently, Hulot et al, reported that the CYP2C19*2 allele is a major determinant in antiplatelet response in patients with myocardial infarction [11]. This has also been reconfirmed by Mega et al, who have shown that patients with the CYP2C19*2 allele require triple the dose of clopidogrel to achieve the same antiplatelet response as patients with the wildtype alleles [12]. Combined data still point to the CYP2C19*2 allele being a major determinant of response.…”
mentioning
confidence: 89%